Videovoci. Interviste a scrittrici - Eleonora Brandigi (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2011)
Videovoci brings together seventeen interviews with writers and artists carried out by the Association Archivio per la memoria e la scrittura delle donne "Alessandra Contini Bonacossi" from 1998 on, within the framework of the project Archivio della scrittura delle donne in Toscana dal 1861 ad oggi (www.archiviodistato.firenze.it/memoriadonne). The publication of Videovoci. Interviste a scrittrici is in fact the result of a ten-year scientific and research project conceived with the aim of valorising the female culture, Italian and other, present in Tuscany. The result of this project takes the form of seventeen speaking biographies: seventeen self-portraits which, with the force of the image and the voice, engage the reader-spectator in a dialogue on the meaning of literary, artistic and political commitment. The video interviews can be consulted at this address: videovoci.fupress.net/